2016
DOI: 10.1186/s12885-016-2057-z
|View full text |Cite
|
Sign up to set email alerts
|

FRAX597, a PAK1 inhibitor, synergistically reduces pancreatic cancer growth when combined with gemcitabine

Abstract: BackgroundPancreatic ductal adenocarcinoma remains one of the most lethal of all solid tumours. Treatment options are limited and gemcitabine-based chemotherapy remains the standard of care. Although growing evidence shows that p21-activated kinase 1 (PAK1) plays a crucial role in pancreatic cancer, its role has not been fully elucidated. This study aimed to characterise the expression and functional relevance of PAK1 in pancreatic cancer.MethodsPAK1 expression was measured in pancreatic cancer specimens by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
(34 reference statements)
6
52
0
Order By: Relevance
“…Furthermore, PAK1 depletion led to reduced migration and invasion suggesting PAK1 may play a more prominent role in KRAS-independent PDAC. In addition, a further study also confirmed that PAK1 depletion led to reduced proliferation in the PDAC cell lines MiaPaCa2 and Panc1 [120]. Thus, whilst it is clear that PAK1 over expression is present in PDAC tissue compared with normal tissue, its precise in vivo role in carcinogenesis and metastatic spread needs to be investigated further.…”
Section: P-21 Activated Kinasesmentioning
confidence: 95%
“…Furthermore, PAK1 depletion led to reduced migration and invasion suggesting PAK1 may play a more prominent role in KRAS-independent PDAC. In addition, a further study also confirmed that PAK1 depletion led to reduced proliferation in the PDAC cell lines MiaPaCa2 and Panc1 [120]. Thus, whilst it is clear that PAK1 over expression is present in PDAC tissue compared with normal tissue, its precise in vivo role in carcinogenesis and metastatic spread needs to be investigated further.…”
Section: P-21 Activated Kinasesmentioning
confidence: 95%
“…One possible impeding factor which is difficult to achieve is the selectivity within the PAK family, because of sequence homology among the family members. Although some Pak1 selective inhibitors like IPA-3 [9,[16][17][18][19], FRAX-597 [11,20], G-5555 [12], and Novartis compound 3 [13] have been disclosed, the successful in vivo dose optimization for target specificity and stability is yet to be tested on larger group of animals. …”
Section: Expert Opinionmentioning
confidence: 99%
“…Recently, several reports [4,9,11,15] unraveled the role of Pak1 in the activation of pancreatic stellate cells (PSCs), its involvement in transforming normal pancreatic cells to PDAC and its ability to modulate drug resistance in pancreatic cancer. All these findings suggest that Pak1-specific inhibitors will prove to be a better adjuvant with the existing chemotherapy modality for PDAC.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAK1 is involved in the tumorigenesis of several types of cancer. For example, downregulating PAK1 expression with a short-hairpin RNA or treatment with the selective PAK1 inhibitor FRAX597 reduced pancreatic cancer cell growth and survival [3]. Moreover, PAK1 expression is upregulated in prostate cancer, and treatment with the mTOR inhibitor rapamycin slowed cancer cell proliferation by inhibiting PAK1 expression [4].…”
Section: Introductionmentioning
confidence: 99%